FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN USAHA MIKRO SEKTOR PANGAN - Dedy Riantoro; Lillyani Margaretha Orisu (Cakrawala Management Business Journal, 2021)
ABSTRACT This studi aims to analyze the effect of working capital, working hours, and length of business on the income of meatball traders in the Wosi and Sanggeng villages, Manokwari Regency. The Method used to collect primary data is a field research method with sample selection using accidental sampling technique. Based on the calculation of SPSS 25.0, the result of the partial test of working capital and working hours showed an effect on the income of meatball traders, while the length of business had no effect on the income of meatball traders in Wosi and Sanggeng Village, Manokwari Regency. Thus, novice entrepreneurs should not hesitate to start their business in trading meatballs in Manokwari, because the income earned will be very large, and there is no need to be afraid to compete with other meatball traders who have been trading in Manokwari for a long time